ANALISIS PENERAPAN MEDIA PEMBELAJARAN AUDIOVISUAL BERBANTU GALLERY WALK DENGAN MODEL PJBL PADA MATERI IPAS DI SEKOLAH DASAR - Kurniawan, Reynaldy Tri; Faradita, Meirza Nanda; Afiani, Kunti Dian Ayu (Ibriez : Jurnal Kependidikan Dasar Islam Berbasis Sains, 2025)
This study aims to describe students’ responses to the use of learning media with the Gallery Walk method within the Project-Based Learning (PjBL) model to support IPAS (Science and Social Studies) learning at the elementary school level. It also seeks to offer an alternative teaching method that can be applied in the classroom. The PjBL model, which often relies solely on presentations, can sometimes lead to student boredom during the learning process. To address this, the study employs a qualitative descriptive approach, with data collected through observation, interviews, and documentation. The research subjects consist of the class teacher and fifth-grade students, focusing primarily on the implementation and impact of audiovisual learning media and the Gallery Walk method within the PjBL framework. The results indicate that students responded positively to the implementation, as seen in their enthusiasm and increased participation throughout the learning process. In conclusion, combining the PjBL model with audiovisual learning media and the Gallery Walk method offers a promising teaching strategy that teachers can apply in the classroom